Study on the Adoption of Online Collaborative Learning from the Perspective of Sociability Quality - Mohamad Hisham, Nur Faaliha Syamie; Salim, Siti Aisyah (Research in Management of Technology and Business, 2023)
Online learning has become more centric in students’ lives nowadays. While sociability quality is one of the challenges with collaborative learning that have been discussed in past studies. Despite numerous studies have explored collaborative learning features, there is still a lack of research that look at sociability quality in the context of online collaborative learning. Therefore, this research aims to identify the relationship between sociability quality dimensions with the adoption of online collaborative learning in higher institutions. This study has collected data from 101 respondents among students in Malaysian higher institutions. The sample was gathered using the quantitative study approach with a series of questionnaires, and online surveys were used to obtain data from respondents. All of the data and quantitative reports in the form of frequency, percentage, mean, and standard deviation were obtained using the Statistical Package for Social Science (SPSS). This study enhances understanding and provides the best technique for improving online collaborative learning in higher institutions. As a result, all variables have a significant relationship with the adoption of online collaborative learning, and social comfort has the highest correlation coefficient with a value of 0.419, referring to the sociability quality dimensions that can provide a positive visual in socialising.